Takht-e Rostam, A Coastal Camp in the Southeast of the Caspian Sea during Late MIS3: A Preliminary Report of Archaeological Excavation - Hosein Ramzanpur; Masoomeh Moradian; Saman Soortiji; Hamideh Amini; Morteza Fattahi (Iranian Journal of Archaeological Studies)
The southern region of the Caspian Sea is regarded as a potential dispersal corridor through which humans migrated from western Eurasia to Central Asia during the Pleistocene epoch. In the last decade, new research has focused on the Palaeolithic archaeology of this area. One significant site is Takht-e Rostam, an open-air Paleolithic location situated west of Neka City in the southeastern part of the Caspian Sea. In 2020, 13 test trenches were excavated as part of a site delimitation project. Takte-e Rostam features a Lower Pleistocene marine terrace landform, surrounded by Late Pleistocene deposits, formed on the Lar limestone formation, rising about 40 to 50 metres above sea level. Palaeolithic artefacts were discovered within a chocolate-coloured sediment deposit. For dating purposes, two soil samples were collected from the excavated trenches and analysed using the OSL method, conducted by the Geophysics Institute, University of Tehran. A total of 2,659 lithic artefacts were recovered from both in situ and secondary layers, underscoring the site’s historical importance. The OSL dating and lithic analyses suggest that the Takht-e Rostam site likely served as a campsite for lithic production and hunting along the coast of the Caspian Sea during the transition from the late Middle to early Upper Palaeolithic periods. Furthermore, the geological landmark of this site may have played an essential role in the hunting strategies of Palaeolithic human groups, and their ability to monitor and dominate the surrounding environment. This research indicates that the deposit’s formation is associated with the Khvalynian stage of the Caspian Sea, with the last layer of loess dating back to marine isotope stage 3.